The application of the similar method in learning Arabic for Indonesian students - Idrus Muchsin Bin Agil (ELITE Association Indonesia, 2023)
Learning Arabic as a second language in Indonesia certainly requires the right methods in teaching it. And in producing a particular method, it is necessary to pay attention to several factors that influence it, including: the background of the learner's language and the foreign language being studied, the student's background, cultural background, the learner's experience in learning Arabic, certain learning objectives or needs (for reading skills, speaking, translating, as well as for the sake of theoretical knowledge of the language), and the allocation of Arabic language teaching (both curriculum and time devoted to teaching foreign languages). In this paper, the author wants to offer a solution to the Arabic language teaching method and explain its application, namely the Al-Musyabahah Method (Cognate Method) for Indonesian students. This method seems to have never been tried in learning Arabic in Indonesia, even though besides being easy this method can also be helpful for novice students who have not mastered much Arabic vocabulary, while they have to learn Arabic. The use of this word equation method is felt to be very appropriate because learning Arabic in Indonesia, namely in Islamic educational institutions, both public and private, generally still focuses on grammatical and translation methods. Keywords: Al-Musyabahah Method, Learning Arabic.